CFD simulations of mixing processes in Direct Injection SI engines - Revadal, Nithin; Ravi Kumar, Subhash (My University, 2021)
To keep up with stringent emission standards and Internal Combustion Engines (ICE) having major market share of all the motor vehicles in the world, it is necessary to explore the avenues to decrease emissions and improve efficiency of the ICE engines. In this thesis the effects of varying piston and fuel temperatures on mixing process and fuel film mass on the piston surface were studied using CONVERGE CFD soft ware. The simulations were performed by selecting a single component (iso-octane) and a multi-component fuel blend (iso-octane, n-hexane, n-decane) as surrogates for gasoline, in a Volvo single cylinder medium tumble 4 valve direct injection engine. Simulations were performed with piston temperatures of 380K,430K, 450K and with fuel temperatures 335K and 363K. The piston temperature played an important role in the quality of mixing, as the higher piston temperature led to faster vaporisation, better mixing. Whereas lower piston temperature caused leaner mixture as some the fuel failed to vaporise. A higher fuel temperature resulted in better mixing with single component fuel, whereas with multi-component fuel and its wide boiling temperature range showed poorer mixing.
Keywords: Internal combustion engines, CFD, simulation, mixing, fuel film mass